Parasitosis intestinal y anemia en niños menores de cinco años de la comunidad de Zungarococha, Iquitos – Perú, 2022 - Marin Aguilar, Maykel Mider (2024)
Intestinal parasitosis and anemia are prevalent problems that have consequences for individual and collective health. The purpose of this study was to investigate the relationship between intestinal parasitosis and anemia in children under 5 years of age belonging to the community of Zungarococha and the jurisdiction of the IPRESS I-2 Zungarococha, during the year 2022. This was a non-experimental, descriptive relational study, with analytical scope, cross-sectional. The sample consisted of 115 children under five years of age from the different population centers of Zungarococha: A.H. 1° de Noviembre (30), Zungarococha (26), Puerto Almendra (21), Ninarumi (38); with prior informed consent. The results determined that the prevalence of intestinal parasitosis (60%) and anemia (28.7%) in children under 5 years of age in the community of Zungarococha. Regarding the degree of parasitic infection, the highest frequency was found to be in the mild degree with 26.1%, with the female sex being the most prevalent. The community of Puerto Almendra had a higher prevalence of parasitosis (66.7%) and anemia (38.1.3%). Using Pearson's Chi-square test with a p-value higher than 0.05%, it was concluded that there is no significant relationship between intestinal parasitosis and anemia in children under five years of age belonging to the community of Zungarococha. With this result, the hypothesis that there is a relationship between parasitosis and anemia is not accepted.